THE PATTERN OF RISING AND FALLING OF SERUM CK-MB IN PATIENTS SUFFERING FROM MYOCARDIAL INFARCTION - DANGI BS; YADAVE BS; PAL V (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Isoenzymes in the blood are important diagnostic and prognostic biomarkers in medical sciences for various cardiac diseases, that is, myocardial infarctions. Creatine kinase (CK)-MB is an important Isoenzyme secret when the destruction of cardiac muscle cells takes place. Methods: A total of 196 myocardial infarction patients and 104 controls were studied in the cardiology department of Hamidia Hospital, Bhopal. Initial elevation of CK-MB occurs after 6 h mean time to peak elevation was 8–24 h and the time to return to the baseline was >48 h in male controls the mean CK-MB level was 19.34±2.83 IU/L and in female the means CK-MB level was 19.32±3.65 IU/L. Result: The mean value of CK-MB at different time intervals in MI patients where 245.12±64.56 at 8–16 h, 230.50±44.88 IU/L at 17–24 h, 88.33±3.84 IU/L at 25–32 h, 74.50±38.19 IU/L at 33–40 h, and 50.88±2.32 IU/L at 41–48 h. Conclusion: The pattern of rising and falling of CK-MB provided most valuable about the MI and its timely management. In conditions where reinfarction is suspected, CK-MB may be useful to classify a new event due to its shorter duration of elevation at detectable levels in plasma.